The Effect of Fall Prevention Education on the Risk of Falls in the Elderly: Pengaruh Edukasi Pencegahan Jatuh Terhadap Risiko Jatuh Pada Lanjut Usia - Widagdo, Wahyu; Mutarobin, Mutarobin; Mumpuni, Mumpuni; Susmadi, Susmadi (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
A fall in the elderly causes a person to suddenly lie down accidentally on the ground or floor or lower level. This condition is often experienced by 1 in 3 elderly people every year. Risk factors for falls in the elderly are behaviour, biological, environmental, and socio-economic. Nurses can make efforts to reduce the risk of falls in the elderly through education for the elderly and their families. The study aimed to determine the extent of the influence of fall prevention educational interventions on the risk of falls in the elderly in the family context. This study used a quasi-experiment, a group pretest post-test, education was carried out using a fall prevention booklet for the elderly in the intervention group and without a booklet in the control group. This research used a purposive sampling method using inclusion criteria to obtain 60 respondents consisting of 30 respondents in the intervention group and 30 respondents in the control group with 6 interactions carried out. The results of this study using the Wilcoxon test from fall prevention education in the intervention group and control group showed a decrease or reduction in fall risk scores (negative rank) in 15 respondents in the intervention group with an average decrease of 8. In the control group, there were 5 respondents experienced a decrease fall risk score, where the average value decreases by 3. The results of this test show the influence of fall prevention education in the elderly on the risk of falls with a p-value <0.001. The conclusion is that educational interventions to prevent falls in the elderly have an impact on reducing risk factors for falls in the elderly. The suggestion is that health education about fall prevention should be given to elderly clients as individuals and groups so that it will reduce risk factors for falls.